2021
DOI: 10.23736/s2724-5683.21.05591-5
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor versus prasugrel in acute coronary syndrome: sex-specific analysis from the RENAMI Registry

Abstract: Background: The use of potent P2Y12 inhibitors (ticagrelor & prasugrel) in acute coronary syndrome (ACS) patients undergoing percutaneous coronary interventions (PCI) is a class I recommendation. We performed a sex-specific analysis comparing the difference in efficacy and safety outcomes between ticagrelor and prasugrel in a real-world ACS population. Methods: Data from the multicentre REgistry of New Antiplatelets in patients withMyocardial Infarction for 4424 ACS patients who underwent PCI and were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…32,33 In addition, in patients with ACS undergoing percutaneous coronary interventions, the use of potent P2Y12 inhibitors (ticagrelor or prasugrel) is a class I recommendation. 34 Shortening the duration of DAPT and switching from ticagrelor or prasugrel to clopidogrel may increase the risk of ischemia in patients with ACS. According to the results of subgroup analysis and the past studies, the short-term DAPT followed by a P2Y12 inhibitors monotherapy may be a good choice for patients with ACS.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 In addition, in patients with ACS undergoing percutaneous coronary interventions, the use of potent P2Y12 inhibitors (ticagrelor or prasugrel) is a class I recommendation. 34 Shortening the duration of DAPT and switching from ticagrelor or prasugrel to clopidogrel may increase the risk of ischemia in patients with ACS. According to the results of subgroup analysis and the past studies, the short-term DAPT followed by a P2Y12 inhibitors monotherapy may be a good choice for patients with ACS.…”
Section: Discussionmentioning
confidence: 99%
“… 39) In the multicenter Registry of New Antiplatelets in patients with Myocardial Infarction (RENAMI) trial enrolled 4,424 ACS patients with PCI it was demonstrated that efficacy or safety of ticagrelor and prasugrel is identical. 78) …”
Section: The P2y 12 Receptor Antagonistsmentioning
confidence: 99%